The creation of social norms under weak institutions [data and replication package] - Diekert, Florian; Eymess, Tillmann; Waichman, Israel; Luomba, Joseph (Universität, 2022)
These data, code, and documents replicate all analyses in "The Creation of Social Norms under Weak Institutions?" by Florian Diekert, Tillmann Eyme...